Application of HEC-RAS for Drainage Capacity Analysis in Sungai Jempol, Negeri Sembilan - Mohammad Yatim, Aminuddin; Abu Talib, Siti Hidayah; Syed Hashim, Syarifah Intan Najla (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Floodplain research is important for human existence and the social economy. It can be observed that the positions of buildings impacted by flooding, such as bridges and roads, cannot be properly matched to the floodplain site in stream floodplain analysis using most computer models. The purpose of this study is to develop an output of Hydrologic Engineering Center’s River Analysis System (HEC-RAS) hydraulic model that will allow for one-dimensional steady flow analysis and stimulate the flood area for 20, 50 and 100 years. This study is applied to Sungai Jempol catchment area, located in Jempol. Floodplain data features such as length of streams, bank position, streamline and cross-sections were used to produce river flow and its cross-sectional shape for each station along the study area. Total of 3 flow rate values were used to indicate an increase in the water level in order to accommodate the additional amount of water that flow into river. The results show that water will overflow into the floodplain at maximum flow rate of 9m3/s or 20 years of return period. The hydraulic model had indicated that 5 out of 30 stations were unable to accommodate the maximum flow rate and thus will led to flooding. By developing the hydraulic model, it clearly shows that the results are more reliable and the affected area can be easily identified. The developed flood model can be a very useful tool in flood management of Sungai Jempol in terms of river development planning, flood mitigation measures, flood evacuation planning and addressing public awareness. This study proved that HEC-RAS is one of effective instrument for analysis and modeling.